EKSISTENSI PAMERAN MINI ART MALANG (MAM) DI KOTA MALANG - Pratama, Rafli Putra Nur; Astawan, I Kadek Yudi (Fakultas Ilmu Budaya, Universitas Brawijaya, 2023)
The Mini Art Malang Exhibition aims to capture the artistic and aesthetic potentials of young artists in Malang City. The Mini Art Malang Exhibition is an exhibition that is an annual art project - an annual art event held by Studio Dinding Luar since 2018. Every year, MAM offers and carries different themes to inject stimuli into young artists which are then interpreted in the form of works of art. MAM participants are not limited to individual works of art or individual creations, but are alsoÂ Â open to communal/community/group based creations in conveying their ideas. The general hope of the MAM event is that the exhibition can become a transmission or medium of communication between artists andÂ appreciators. This article discusses the history of the founding of Mini Art Malang (MAM) starting from the background of its formation, goals, and achievements.